Examining the impact of shocks to tourist arrivals in ASEAN countries by using nonlinear methods² - Li Jingyi (Universiti Malaysia Sabah, 2021)
This paper uses a set of nonlinear methods, such as the Fourier fractional integration test (Gil-Alana and Yaya, 2020), to examine impact of shocks to international tourist arrivals in ASEAN countries. These nonlinear methods indicated that the findings are mixed.